Long-Term Ambient Storage and Retained Hypnotic–Sedative Activity of a Confiscated Mitragyna speciosa Specimen: A Forensic Chemical and Pharmacological Evaluation - Supiyani; Sarah Salsabil (Journal of Chemical Natural Resources, 2025)
Mitragyna speciosa (kratom) is a Southeast Asian medicinal plant whose principal alkaloid, mitragynine, exhibits stimulant and sedative properties. Long-term preservation of bioactive constituents in stored plant material is a quality control concern. This study investigated alkaloid stability and pharmacological recoverability of M. speciosa leaf powder stored under ambient, uncontrolled conditions for over ten years following confiscation in 2016. Three extraction solvents, ethanol, acetone, and water–methanol, were employed and their phytochemical profiles compared by Thin-Layer Chromatography with iodoplatinate visualization and Gas Chromatography–Mass Spectrometry (GC–MS). Phytochemical screening revealed consistent presence of alkaloids, sterols, triterpenoids, fatty acids, terpenoids, phenolics, and nitrogen-containing heterocycles across all solvent systems. Acetone yielded the highest relative mitragynine content (8.52%) compared with ethanol (7.01%) and water–methanol (3.64%). Preserved pharmacological activity of the acetone extract was confirmed in vivo using the glass cylinder escape latency test in male mice (Mus musculus), demonstrating a statistically significant, concentration-dependent hypnotic–sedative effect across doses of 4.5–114 mg/kg. One-way ANOVA with Tukey's HSD and Duncan's post hoc tests revealed statistically significant differences among treatment groups (p < 0.001). Within the limitations of this single-specimen evaluation, findings indicate that a detectable alkaloid profile and measurable hypnotic–sedative activity of M. speciosa are retained over extended ambient storage, with solvent selection influencing relative mitragynine recovery; absolute quantification and comparison with a fresh reference specimen were not possible and are recommended. This study provides reference data for forensic evaluation of aged kratom specimens and underscores the need for standardized storage and quality control protocols for kratom preparations.